Molecular signature induced by RNASET2, a tumor antagonizing gene, in ovarian cancer cells - Acquati, Francesco (Impact Journals LLC, 2011)
Using the Hey3Met2 human ovarian cancer cell line, we previously found the RNASET2 gene to possess a remarkable in vivo tumor suppressor activity, although no in vitro features such as inhibition of cell proliferation, clonogenic potential, impaired growth in soft agar and increase in apoptotic rate could be detected. This is reminiscent of the behavior of genes belonging to the class of tumor antagonizing genes (TAG) which act mainly within the context of the microenvironment. Here we present transcriptional profiles analysis which indicates that investigations of the mechanisms of TAG biological functions require a comparison between the in vitro and in vivo expression patterns. Indeed several genes displaying a biological function potentially related to tumor suppression could not be validated by subsequent in vivo expression analysis. On the other hand the fact that we could find congruency for three genes both in vivo and in vitro adds a warning to a too much stringent categorization of this class of genes which relies on the sensitivity of the methodological approaches.